Stardom and Talent - Adler, Moshe (American Economic Review, 2016)
The Economics of Superstars sets out to explain the relationship between talent and success in the arts, but there is no agreement about what this relationship is. But whatever its other features may be, superstardom means that market output is concentrated on just a few artists. Concentration always raises the question of efficiency. Superstardom may be inefficient not only because it raises prices for consumers but also because it deprives other artists of the opportunity to practice art. Artists who do not practice art lose psychic income. Because psychic income cannot be transferred from one person to another, the loss of this income may be inefficient. This chapter reviews theories of superstardom and theories about the emergence of stars. The efficiency of superstardom is discussed in terms of effects on consumers and the use of publicity rights by the star. The chapter goes on to deal with the loss of opportunities to practice art that are caused by superstardom and suggests ways to alleviate the problem. Finally the empirical literature that tests the different theories of superstardom is reviewed.